The 14-Ton Giant Underwood Master operating daily at the New York World's Fair 1939 (Colourpicture)
The Giant Underwood Master Typewriter, the largest in the world, operates daily at the Underwood Elliott Fisher Exhibit in the Business Systems and Insurance Building at the New York World's Fair